2020
DOI: 10.1093/ehjci/jeaa075
|View full text |Cite
|
Sign up to set email alerts
|

Progression of aortic stenosis and echocardiographic criteria for its severity

Abstract: Aims  Guidelines-recommended criteria for identifying severe aortic stenosis (AS) are based on small, homogenous cohorts of patients, leading to potentially inconsistent or missed diagnosis. We used a large cohort of patients with varying degrees of AS to (i) characterize its progression; (ii) evaluate the influence of demographic and echocardiographic variables; and (iii) derive haemodynamically consistent cut-off values. Methods and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…In nearly 75% of those with low‐flow states by 2D‐TTE, a normal SV was calculated using 3D‐TEE methods. The analysis of the fitted curves for data pairs AVA and MPG confirmed that 2D‐TTE AVA overestimates the severity of AS, with a an AVA of 1 cm 2 being related to a MPG well below the 40 mm Hg cutoff reported in current guidelines, in line with previously reported data 5,19 . Similarly to what observed with MDCT, both 3D‐TEE imaging modalities showed a reduction in the proportion of patients with low‐gradient and pathological AVA, as well as better agreement between AVA and MPG with current guidelines cutoff values.…”
Section: Discussionsupporting
confidence: 87%
“…In nearly 75% of those with low‐flow states by 2D‐TTE, a normal SV was calculated using 3D‐TEE methods. The analysis of the fitted curves for data pairs AVA and MPG confirmed that 2D‐TTE AVA overestimates the severity of AS, with a an AVA of 1 cm 2 being related to a MPG well below the 40 mm Hg cutoff reported in current guidelines, in line with previously reported data 5,19 . Similarly to what observed with MDCT, both 3D‐TEE imaging modalities showed a reduction in the proportion of patients with low‐gradient and pathological AVA, as well as better agreement between AVA and MPG with current guidelines cutoff values.…”
Section: Discussionsupporting
confidence: 87%
“…Disease progression was also found to occur more rapidly in Caucasians than African Americans (decrease in AVA cm 2 /year 0.075±0.005 in Caucasians vs 0.062±0.004 in African Americans, p=0.03). This finding may be attributable to the higher prevalence of bicuspid aortic valve in Caucasians than in the general population 23…”
Section: Epidemiology and Progression Of Moderate Asmentioning
confidence: 93%
“…In a 1997 prospective study by Otto et al, 20 123 patients with asymptomatic mild to moderate AS followed for 2–3 years had an annual increase in Vmax of 0.32±0.34 m/s, increase in MPG of 7±7 mm Hg and decrease in AVA of 0.12±0.19 cm 2 /year. More recent studies suggest a slower annual progression of AS with Vmax increase of 0.24±0.3 m/s, increase in MPG of 3.2–6.4 mm Hg and decrease in AVA of 0.068±0.004 cm 2 /year 5 20–23…”
Section: Epidemiology and Progression Of Moderate Asmentioning
confidence: 98%
See 2 more Smart Citations